Peran Keluarga dan Jarak Tempuh Fasyankes Terhadap Kepatuhan Pasien Gagal Ginjal Kronik Dalam Melaksanakan Program Hemodialisis: The Role of Family and Distance to Healthcare Facilities in Chronic Kidney Failure Patient Compliance in Carrying Out Hemodialysis Programs - Didih Sutendi; Weslei Daely (Journal of Nursing Education and Practice, 2022)
Background: Hemodialysis is one of the therapies used for chronic kidney failure (CKD) apart from diet and fluid management and kidney transplantation. In addition to the distance from a health facility to the residence of a patient with CKD to carry out HD, there is a role for the family in carrying out the hemodialysis program. Objective: This study aims to determine the relationship between the role of the family and the distance of health facilities to the compliance of patients with chronic kidney failure in carrying out the hemodialysis program at Leuwiliang Hospital. Methods: The method used in this study is to use the concept of quantitative research using cross-sectional methods, carried out on a sample of 43 patients at Leuwiliang Hospital taken by a total sampling technique. Instrument in data collection using a questionnaire. Statistical test using chi-square. Results: The results showed that the compliance of patients with chronic kidney failure in carrying out the hemodialysis program in the hemodialysis room averaged 79.1%. The average family role is good as much as 81.4%. The average distance for health facilities from far away patients is 69.8%. The results of statistical tests showed that the relationship between the role of the family on the compliance of patients with chronic kidney failure in carrying out the hemodialysis program at the Leuwiliang Hospital (P-Value = 0.006 < 0.05) with an OR value of 12.9 and the relationship between the distance of health facilities and the compliance of patients with chronic kidney failure. in implementing the hemodialysis program at Leuwiliang Hospital (P-Value = 0.699 < 0.05) with an OR value of 0.597. Conclusion: There is a relationship between the role of the family in the compliance of chronic kidney failure patients in carrying out the hemodialysis program at Leuwiliang Hospital and there is no relationship between the distance traveled by health facilities to the compliance of chronic kidney failure patients in carrying out the hemodialysis program at Leuwiliang Hospital.